THE ALTERNATIVE RECREATION SOCIETY IN THE CITY OF PEKANBARU (STUDIES ABOUT THE FUNCTION IN THE STADION UTAMA RIAU AS A MEANS OF RECREATION) - Rana, Eldis; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In this modern times, the level of the needs of human life more varied. Not only food, cloth and board to the main needs of the community’s city. But the city will seek this type of other necessities if the needs of the main have been fulfilled. One of them is to meet the needs in the field of entertainment and recreation. Therefore the city of Pekanbaru have some place of recreation, such us : The Recreation Park of Alam Mayang, The Park of Putri Kacang Mayang, a City Park, The City Forest, The Museum of Sang Nila Utama, The Full MTQ and The Art of Idrus Tintin, The Monument Locomotive and etc. Recreation has become an essential element in the life of modern society or urban areas. Income, the conditions of work and the development of transportation that is getting better has been giving people more money, time and mobility is higher for doing recreation. Naturally, human beings are capable of creating a place of recreation of her or his own. Humans create a place of recreation, because of narrow space open public in the city of Pekanbaru. Place recreation is available was still can not give satisfaction for the city of Pekanbaru. To that end, every society and individuals will be looking for something new, or a new, as well as places that feels could be their recreation alternative. This is what makes people interested in visiting the Stadion of Riau are beginning to function as facilities and infrastructure the sport to the show will complete for the 2012, even changing the function of a place where an alternative society because the grandeur of the building and the location for doing recreation, such as sports or just a place of young man or girls. Altough visitors to the Stadion of Riau are aware of punishment that is like the lighting at night, the lack of management of hygiene and management supervision, but visitors can just ignore it because visitors more concerned with rewards that they can, like not the cost, the recreation not so far from the visitors residence, as well as the venue of the Stadion Utama Riau and the existence of its own for the society of Riau. The recreation that most often by visitors in the Stadion of Riau is the activity of the food and beverage, the activities of the game and sports, as well as activities of youth.Keywords : Recreation, Society, and Over the Function.